IMPLEMENTATION OF PROBLEM BASED LEARNING (PBL) TO IMPROVE CRITICAL THINKING ABILITY AND MATHEMATICS LEARNING OUTCOMES - Tekad Pramono; Suhandi Astuti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Based on the results of the TIMSS-R study (2015), students' critical thinking skills in Indonesia are still low. This is due to the lack of variation in the learning model used. Therefore, the research conducted aims to improve students' critical thinking skills and mathematics learning outcomes through the Problem Based Learning (PBL) model. The subject of this research was grade 5 SDN Pledokan District Semarang with the total of 16 students (8 male students and 8 female students). This research was a classroom action research with 2 learning cycles. Data collection was carried out using questionnaire critical thinking instruments and test questions for student learning outcomes in mathematics subjects. The technique of analyzing data used was comparative descriptive analysis pre-cycle, cycle I and cycle II. The results of this study were an increase in the ability of students from pre cycle, cycle I and cycle II. In the pre-cycle conditions of critical thinking skills of students in the high category 18.75%, 37.5% in the moderate category, and 43.75% in the low category, in the first cycle there was an increase in the high category 31.25%, the moderate category 56.25% and in the low category 18.75%, in the second cycle again increased to the high category 43.75%, the medium category 50% and the low category 6.25%. Completeness of student learning outcomes in mathematics in pre-cycle reaches KKM only 37%, then in the first cycle increased to 43.75% and in the second cycle again increased to 75%. Based on these data, there is an increase in critical thinking skills in each category and an increase in student outcomes by 38%.